THE POSSIBILITY STUDY OF BRIQUETTING AGRICULTURAL WASTES FOR ALTERNATIVE ENERGY - Gunjan Patil (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2019)
Globally energy crisis is known as a new era’s biggest problem. The use of agricultural wastes into the form of briquettes are the best alternative option of renewable energy sources. This paper studies the possibility of utilizing agricultural wastes into briquetting production with high calorific value. Major wastes were sugarcane bagasse, coffee husk, wheat straw, peanut shells, rice husks, paddy straw, corn stalks, sunflower stalk, soybean husk, coir pitch, jute sticks, caster seed shells, mustard stalks, cotton stalks and tobacco wastes for energy in the form of briquettes biomass. Observations were taken from Department of Bioenergy, Tamil Nadu Agriculture University, Coimbatore (Tamil Nadu), India of different raw materials and briquettes of those raw materials. Results show that there were very satisfactory results after evaluation. In general, calorific value briquettes is higher than those of raw materials. Raw materials of agricultural wastes and forest residual wastes ranged from 1,200-3,000 Kcal/Kg and its calorific values are significantly higher in briquettes than raw materials. Raw material of rice husk produces 3,000 Kcal/kg and briquettes of rice husk produces 3200 Kcal/kg. Likewise differences were observed in all types of agricultural wastes. The input and output ratio ware observed as cost-effective and profitable in all parameters for the farmers. Briquetting production is the emerging, ecofriendly, cost effective and profitable technology for the use of agricultural residues. It may help farmers to improve its socio-economic status and proper reuses of agricultural wastes.